Service discovery mechanism for service continuity in heterogeneous network / Shaifizat Mansor ...[et al.] - Mansor, Shaifizat; Kamal Basha, Nor Shahniza; Muhamat Dawam, Siti Rafidah; Ali, Noor Rasidah; Elias, Shamsul (2015)
The service discovery process would greatly boost the ability of service lookup to realize the similar services across different platforms. As mobile devices are able to support more than one interface in a single device, the ability to use application services continuously with minimal interruptions becomes a major challenge. Service discovery limitations and future requirements mobile services are presented. To provide a seamless services, an adaptive approach of dynamic service discovery in future mobile environment is proposed to assist the service discovery process smoothen the service discovery and consumption of services